2018
DOI: 10.1016/j.str.2018.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Basis for Membrane Recruitment by the PX and C2 Domains of Class II Phosphoinositide 3-Kinase-C2α

Abstract: Phosphorylation of phosphoinositides by the class II phosphatidylinositol 3-kinase (PI3K) PI3K-C2a is essential for many processes, including neuroexocytosis and formation of clathrin-coated vesicles. A defining feature of the class II PI3Ks is a C-terminal module composed of phox-homology (PX) and C2 membrane interacting domains; however, the mechanisms that control their specific cellular localization remain poorly understood. Here we report the crystal structure of the C2 domain of PI3K-C2a in complex with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 63 publications
1
36
1
Order By: Relevance
“…In solution, the carboxyterminal PX-C2 module of PI3K-C2α folds back onto the kinase domain, thereby inhibiting membrane binding and catalytic activity. Only when recruited to the plasma membrane through its N-terminal interaction with clathrin 147,148 will cooperative binding to PI(4,5)P2 by the PX- 149 and C2-domain 150 unlock PI3K-C2α catalytic activity 146 (FIG. 4a).…”
Section: Activation Of Class II Pi3ksmentioning
confidence: 99%
“…In solution, the carboxyterminal PX-C2 module of PI3K-C2α folds back onto the kinase domain, thereby inhibiting membrane binding and catalytic activity. Only when recruited to the plasma membrane through its N-terminal interaction with clathrin 147,148 will cooperative binding to PI(4,5)P2 by the PX- 149 and C2-domain 150 unlock PI3K-C2α catalytic activity 146 (FIG. 4a).…”
Section: Activation Of Class II Pi3ksmentioning
confidence: 99%
“…PI3K effectors (class 2): The group of PI3K contains several domains with the ability to be associated to the PM, such as C2, the PX, and the PI3K_C2 domains. Recent biochemical studies have shown cooperative binding of the C2 and PX domains with affinities in complex with different phosphoinositides in the range of 4.5 to 52 μM [50]. An important source of phosphoinositide production at the PM are PI3K's themselves.…”
Section: Raf Effectors (Class 1)mentioning
confidence: 99%
“…Similar to the Class I PI3K p110s, these enzymes possess RBD, C2, helical and catalytic domains, but also possess a poorly‐structured N‐terminal region, in addition to a C‐terminal region containing C2 and PX domains [14,95]. Understanding of Class II PI3K regulation is in its infancy, but for PI3KC2α, the N‐terminal region has been shown to support plasma membrane recruitment of the enzyme via interactions with clathrin [96,97], while the C2 and PX domains interact with phosphoinositides such as PtdIns(4,5)P 2 to release an autoinhibitory mechanism to enable catalytic activity [98–100]. It is likely that multiple further interactions with proteins and lipids can regulate the function of the Class II PI3Ks and, as for the Class I PI3Ks, specificity within such interactions is likely to guide differential usage of the three Class II isoforms [93].…”
Section: Class II Pi3ksmentioning
confidence: 99%